Targeting Ferroptosis Holds Potential for Intervertebral Disc Degeneration Therapy - Jiaxing Chen; Xinyu Yang; Yi Feng; Qiaochu Li; Jingjin Ma; Linbang Wang; Zhengxue Quan (Cells, 2022)
Intervertebral disc degeneration (IVDD) is a common pathological condition responsible for lower back pain, which can significantly increase economic and social burdens. Although considerable efforts have been made to identify potential mechanisms of disc degeneration, the treatment of IVDD is not satisfactory. Ferroptosis, a recently reported form of regulated cell death (RCD), is characterized by iron-dependent lipid peroxidation and has been demonstrated to be responsible for a variety of degenerative diseases. Accumulating evidence suggests that ferroptosis is implicated in IVDD by decreasing viability and increasing extracellular matrix degradation of nucleus pulposus cells, annulus fibrosus cells, or endplate chondrocytes. In this review, we summarize the literature regarding ferroptosis of intervertebral disc cells and discuss its molecular pathways and biomarkers for treating IVDD. Importantly, ferroptosis is verified as a promising therapeutic target for IVDD.